Off season cultivation of cucurbits under polytunnel with plastic and straw mulch - Kumari , Mamta (Journal of Postharvest Technology, 2018)
A field experiment was carried out in two consecutive Rabi seasons to study the effect of different mulch for off season cultivation of vegetables particularly cucurbits. The result showed that poly tunnel was the best treatment and with the help of poly tunnel cucurbits can be grown successfully winter season. The highest yield of cucurbits was found i.e.136.84 q ha from the crop grown under polytunnel with the highest BC ratio i.e.1; 1.94. Hence, for off season cultivation of cucurbits farmers can adopt polytunnel.